A novel device for detecting anaerobic threshold using sweat lactate during exercise - Seki, Yuta; Nakashima, Daisuke; Shiraishi, Yasuyuki; Ryuzaki, Toshinobu; Ikura, Hidehiko; Miura, Kotaro; Suzuki, Masato; Watanabe, Takatomo; Nagura, Takeo; Matsumato, Morio; Nakamura, Masaya; Sato, Kazuki; et al. (Scientific reports, 2021)
The lactate threshold (LT1), which is defined as the first rise in lactate concentration during incremental exercise, has not been non-invasively and conveniently determined in a clinical setting. We aimed to visualize changes in lactate concentration in sweat during exercise using our wearable lactate sensor and investigate the relationship between the lactate threshold (LT1) and ventilatory threshold (VT1). Twenty-three healthy subjects and 42 patients with cardiovascular diseases (CVDs) were enrolled. During exercise, the dynamic changes in lactate values in sweat were visualized in real-time with a sharp continuous increase up to volitional exhaustion and a gradual decrease during the recovery period. The LT1 in sweat was well correlated with the LT1 in blood and the VT1 (r = 0.92 and 0.71, respectively). In addition, the Bland–Altman plot described no bias between the mean values (mean differences: − 4.5 and 2.5 W, respectively). Continuous monitoring of lactate concentrations during exercise can provide additional information for detecting the VT1.